Ethylene Potentiates Sulfur-Mediated Reversal of Cadmium Inhibited Photosynthetic Responses in Mustard - Khan, Nafees A.; Asgher, Mohd; Per, Tasir S.; Masood, Asim; Fatma, Mehar; Khan, M. I. R. (Frontiers in Plant Science, 2016)
The potential of exogenous ethylene and sulfur (S) in reversal of cadmium (Cd)-inhibited photosynthetic and growth responses in mustard (Brassica juncea L. cv. Pusa Jai Kisan) were studied. Plants grown with 50 µM Cd showed increased superoxide and H2O2 accumulation and lipid peroxidation together with increased activity of 1-aminocyclopropane carboxylic acid synthase (ACS) and ethylene production and inhibition of photosynthesis and growth. Application of 1 mM SO42− or 200 µL L−1 ethephon (ethylene source) influenced photosynthetic and growth performance equally in presence or absence of Cd. However, their combined application synergistically improved photosynthetic performance more in presence of Cd and reduced oxidative stress (lower superoxide and H2O2 accumulation) by decreasing ethylene and glucose sensitivity with the increase in cysteine and methionineand a non-proteinogenic thiol (reduced glutathione; GSH) contents. The central role of ethylene in potentiating S-mediated reversal of Cd-induced oxidative stress was evident with the use ethylene action inhibitor, norbornadiene (NBD). The application of NBD resulted in decreased thiol production and photosynthetic responses. This suggests that ethylene promotes the effects of S in reversal of adverse effects of Cd, and thus, ethylene modulation may be considered as potential tool to substantiate the S effects in reversal of Cd inhibited photosynthesis and growth in mustard.